2019
DOI: 10.5964/ejop.v15i4.1759
|View full text |Cite
|
Sign up to set email alerts
|

The High Five Model: Associations of the high factors with complete mental well-being and academic adjustment in university students

Abstract: Traditionally, models of positive personality traits have referred to moral characteristics. The High Five Model (HFM) is a factor model of individual positive traits based on an inductive psycho-lexical approach. Unlike other models, in the HFM the positive characteristics were freely determined by lay people, beyond any moral tones. The HFM comprises the following factors: erudition, peace, cheerfulness, honesty, and tenacity, known as “the high factors.” This model was shown to positively exceed the capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(29 citation statements)
references
References 53 publications
4
19
2
4
Order By: Relevance
“…En términos generales, los rasgos positivos comentados (erudición y tenacidad) tenían un efecto protector sobre el bienestar psicológico. Este resultado confirma asimismo los hallazgos previos realizado con este mismo modelo de rasgos positivos en ocasión de predecir el ajuste académico a la vida universitaria (Castro Solano & Cosentino, 2019). Malignismo (e.g., corrupto, embusteros, malintencionado) es el rasgo negativo más vinculado conceptualmente con su equivalente maquiavelismo y psicopatía de la Tríada Oscura.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…En términos generales, los rasgos positivos comentados (erudición y tenacidad) tenían un efecto protector sobre el bienestar psicológico. Este resultado confirma asimismo los hallazgos previos realizado con este mismo modelo de rasgos positivos en ocasión de predecir el ajuste académico a la vida universitaria (Castro Solano & Cosentino, 2019). Malignismo (e.g., corrupto, embusteros, malintencionado) es el rasgo negativo más vinculado conceptualmente con su equivalente maquiavelismo y psicopatía de la Tríada Oscura.…”
Section: Discussionunclassified
“…Particularmente, los rasgos paz y jovialidad eran los rasgos más fuertemente asociados con el bajo riesgo de contraer tanto enfermedades médicas como psicológicas. En otro estudio realizado con estudiantes universitarios se pudo verificar que los factores altos, además de ser promotores del bienestar psicológico, permitían predecir tanto la adaptación a la vida universitaria como el rendimiento académico de los estudiantes (Castro Solano & Cosentino, 2019). En este caso, la tenacidad y la erudición eran los dos factores de personalidad positivos más fuertemente asociados con la percepción de ajuste a la vida universitaria.…”
Section: Bienestar Y Modelos De Personalidad Positiva Y Negativaunclassified
See 1 more Smart Citation
“…In this context, HFM factors can be considered as the positive poles of BFM. Castro Solano and Cosentino ( 2019 ) posit that the positive traits or high factors of the HFM are relatively stable within each individual and are represented by positive psychological characteristics. Moreover, the high factors of the HFM possess certain notable attributes: they can be measured, vary among individuals, and may increase or decrease due to internal or external influences.…”
Section: Introductionmentioning
confidence: 99%
“…Among its findings, it has been observed that HFM factors, as positive personality traits, are negatively associated with health indicators and positively correlated with emotional, psychological, and social wellbeing. (Castro Solano and Cosentino, 2019 ) have also demonstrated HFM's association with elements of the academic context and academic performance, utilizing self-reported values by students for performance analysis. In their study, it was found that the high factors of tenacity and erudition were the only ones positively associated with academic performance.…”
Section: Introductionmentioning
confidence: 99%